ANALISIS YURIDIS PENERBITAN SURAT PERINTAH PENGHENTIAN PENUNTUTAN OLEH KEJAKSAAN DIKAITKAN DENGAN ASAS OPORTUNITAS DAN UNDANG-UNDANG NO 16 TAHUN 2004 TENTANG KEJAKSAAN RI - Ferdy Saputra; Syafrddin Kalo; Mahmud Mulyadi; Muhammd Hamdan (USU LAW JOURNAL, 2014)
ABSTRACTProsecutors acting prosecuting a person suspected of committing crimes is based on Article 8 paragraph (2) of Law No. 16 of 2004 on the Attorney RI. In prosecuting attorney acting for and on behalf of the State. To prosecute a person suspected of committing a crime, the prosecutor is allowed to waive the case in the public interest pursuant to Article 35 letter c. Law No. 16 of 2004 on the Attorney RI. On the other hand the prosecuting attorney must uphold the principle of equality before the law. Authority to waive the case prosecutor apparently misused by the Attorney on specific cases. For example: Case BLBI and Bibit-Chandra case. Setting principles and opportunity in the Code of Criminal Procedure Law. 16 Year 2004 on Indonesian Attorney can not give an explanation although expressly recognized the principle of opportunity. Criminal Procedure Code recognizes the principle of opportunity, however, the Criminal Code does not provide an explanation about this. While in Law. 16 of 2004 on the Attorney RI, the principle of opportunity provided for in Article 35 letter c as the authority of the Attorney General in the case of a waiver in the public interest. Regarding the public interest itself also still can cause a variety of different interpretations due to the Criminal Procedure Code and the Law. 16 Year 2004 on Indonesian Attorney formulate the common definition is too broad and should be returned or refer to the ideals of the law or of the nation as expressed in the preamble of the 1945 Constitution of the Republic of Indonesia. The results showed that: Should termination prosecution done really pay attention to grounds for termination of prosecution; Better regulation principles set opportunity in more detail and specific especially in providing the sense of "the public interest", and should provide limits understanding of the categories included in "the interests of general ".Key Words : Termination of prosecution; Termination of investigation, and the interest of the public.